2010
DOI: 10.2147/opth.s12441
|View full text |Cite
|
Sign up to set email alerts
|

Dose uniformity of topical corticosteroid preparations: difluprednate ophthalmic emulsion 0.05% versus branded and generic prednisolone acetate ophthalmic suspension 1%

Abstract: PurposeTo compare the dose uniformity of difluprednate ophthalmic emulsion 0.05% (Durezol®) with both branded and generic prednisolone acetate ophthalmic suspension 1% under different simulated patient usage conditions.MethodsDrug concentrations of difluprednate emulsion, branded prednisolone acetate suspension (Pred Forte®) and generic prednisolone acetate suspension following three storage conditions (upright, then shaken; upright, not shaken; inverted, not shaken) were analyzed by high performance liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 5 publications
0
34
1
Order By: Relevance
“…Notably, prednisolone acetate is a suspension that requires shaking before use, 11 whereas difluprednate emulsion does not. 24 One study 25 found that even with shaking (using a wristaction mechanical shaker at six cycles per second) only 40% of the prednisolone acetate concentrations were within 15% of the declared concentration compared with 100% for the difluprednate concentrations. Furthermore, prednisolone acetate contains benzalkonium chloride, a preservative that has been associated with allergies, tear film instability, disruption of the corneal epithelium barrier, and damage to deeper ocular tissues in clinical or preclinical investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, prednisolone acetate is a suspension that requires shaking before use, 11 whereas difluprednate emulsion does not. 24 One study 25 found that even with shaking (using a wristaction mechanical shaker at six cycles per second) only 40% of the prednisolone acetate concentrations were within 15% of the declared concentration compared with 100% for the difluprednate concentrations. Furthermore, prednisolone acetate contains benzalkonium chloride, a preservative that has been associated with allergies, tear film instability, disruption of the corneal epithelium barrier, and damage to deeper ocular tissues in clinical or preclinical investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were tapered off the study medication during days 14 to 27 at the discretion of the investigator. On day 14, the first day after completion of the planned treatment course, individuals who responded satisfactorily began graduated tapering of study drug, successively halving the number of doses per day at each step (steps were at days 14-20, days 21-24, and days [25][26][27]. If further tapering was required after day 28, the study drug was to be discontinued and a suitable drug prescribed as deemed appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…8 Emulsions, such as difluprednate 0.05%, and gel formulations may therefore be preferred to suspensions because of the accuracy that they offer from dose to dose. 24,25 Inclusion in the current study of aphakic infants treated with a contact lens is important, as contact lens use is commonly used for correction of aphakia in infants. 1 In this study, application of the study medication in the affected eye was possible while the contact lens remained in place.…”
Section: Discussionmentioning
confidence: 99%
“…In the two studies, eligible patients were randomised 1:1 stratified by center to receive either difluprednate 0.05% QID alternating with vehicle QID or prednisolone acetate 1% 8 times daily for 14 days. At the discretion of the investigator, gradual tapering of the dosage was initiated on day 14 in patients who satisfactorily responded by successively halving the number of daily doses in a stepwise manner (steps were at days 14-20, 21-24, and [25][26][27]. The study drug was discontinued if further treatment was required after day 28, and a suitable alternative drug was prescribed.…”
Section: Methodsmentioning
confidence: 99%
“…9,25 In addition, difluprednate has been reported to have better dose uniformity than branded and generic prednisolone acetate suspensions under various storage conditions. 26 Moreover, the preservative system used in difluprednate emulsion (sorbic acid) may cause only minimal damage or irritation to the ocular surface, particularly in patients with existing ocular surface disease, unlike benzalkonium chloride (BAK) preservative. BAK is a common ophthalmic preservative system which has been shown to disrupt the tear film and cause direct toxicity to both corneal and conjunctival epithelial cells.…”
Section: 15mentioning
confidence: 99%